Modélisations multi-scalaires des dynamiques urbaines dans la longue durée : l’exemple du quartier abbatial de Vendôme (41) - Gaël Simon (Unité Mixte de Recherche 8504 Géographie-cités, 2012)
The dynamics of the material reality of a city are complex to apprehend. The modelings suggested until now concern only one scale of analysis, either the one of the city or the one of the urban fabric. These two levels of analysis had never been crossed. This article seeks to assert the principles and basis of reflection for a multi-scalar modeling through the study of the abbey district of Vendôme between the 11th and 18th centuries. Although no historical interpretations could be advanced for the moment, the method implemented offers interesting potentialities to apprehend the multi-scalar relations. The cartography and the chronography are used to represent spatial dynamics of this district.